2015
DOI: 10.1002/jat.3210
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorinated chemicals, PFOS and PFOA, enhance the estrogenic effects of 17β‐estradiol in T47D human breast cancer cells

Abstract: Perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA) are the two most popular surfactants among perfluorinated compounds (PFCs), with a wide range of uses. Growing evidence suggests that PFCs have the potential to interfere with estrogen homeostasis, posing a risk of endocrine-disrupting effects. This in vitro study aimed to investigate the estrogenic effect of these compounds on T47D hormone-dependent breast cancer cells. PFOS and PFOA (10(-12) to 10(-4)  M) were not able to induce estrogen resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 72 publications
(97 reference statements)
0
21
0
2
Order By: Relevance
“…reported that PFOS and PFOA have estrogenic activity and antithyroid hormone activity, altering steroid hormone synthesis and the expression of the major steroidogenic genes . On the other hand, another in vitro study, which analyzed PFOA and PFOS estrogenic effects on T47D hormone‐dependent BC cells, found that while these compounds did not have estrogenic activity, they enhanced the effects of estradiol on estrogen‐responsive gene expression, ERK1/2 activation and the growth of the hormone‐deprived T47D cells …”
Section: Discussionmentioning
confidence: 99%
“…reported that PFOS and PFOA have estrogenic activity and antithyroid hormone activity, altering steroid hormone synthesis and the expression of the major steroidogenic genes . On the other hand, another in vitro study, which analyzed PFOA and PFOS estrogenic effects on T47D hormone‐dependent BC cells, found that while these compounds did not have estrogenic activity, they enhanced the effects of estradiol on estrogen‐responsive gene expression, ERK1/2 activation and the growth of the hormone‐deprived T47D cells …”
Section: Discussionmentioning
confidence: 99%
“…In hormone-dependent T47D human breast cancer cells, neither PFOA nor PFOS, by themselves, affected cell proliferation. However, in the presence of estradiol, both chemicals did enhance the effects of estradiol on cell growth as well as the expression of several estrogen-responsive genes and ERK1/2 activation [ 382 ].…”
Section: Evidence Linking Environmental Factors and Breast Cancermentioning
confidence: 99%
“…10 Both perfluorinated alkylated substances have been shown to enhance the estrogenic effect of estradiol in vitro. 11 There is also some evidence that PFOS and PFOA could affect estrogen homeostasis during human pregnancy. 12 LC-MS/MS method development.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…Exposure to xenoestrogens may also be a risk factor for hormone-related cancers including those of breast and the reproductive tract, especially during the sensitive, early developmental stages. [11][12][13] The proper assessment of combinatory effects of multiple xenoestrogens are a current key challenge. Numerous studies investigating the potency of individual compounds or compound classes have been published, while data on estrogenic mixtures is scarce.…”
mentioning
confidence: 99%